Patient handling complaint strategies for health facilities and services at PKU Muhammadiyah Yogyakarta Hospital - Afkar Ulwan Khasyarahman, Muhammad; Santoso, Eka Budy; Putranto , Ade (Universitas Ahmad Dahlan, 2023)
Through an effective complaint handling process, information from customers will be obtained as input in improving and developing agency service activities. Complaints are a form of dissatisfaction with information or services received. Thus, complaints can solve customer dissatis faction problems in hospital services to improve hospital quality. This study aims to evaluate the effectiveness of handling complaints at the PKU Muhammadiyah Yogyakarta Hospital. This research is qualitative. Subjects in the study were ten officers who often handled complaints. The study was conducted in 21 August-September 2023 at PKU Muhammadiyah Yogyakarta Hospital. The availability of supporting facilities is adequate, including complaint channels via SMS, email, via telephone, suggestion box, complaint sheet. All staff have received training in effective communication. The flow and procedures for handling complaints have been maximized. However, their many complaints are still repeated. The process of monitoring and evaluating complaint han- dling reporting documentation has been running optimally. The response time for handling complaints is perfect because all cases are handled on average 1x24 hours, the response time reaches 95%. The handling of complaints at the PKU Muhammadiyah Yogyakarta Hospital has been maximized but ineffective. The handling is not yet effective because the information system process does not support the complaint handling process, for example, the delivery of information to patients who have not been able to in realtime. The mechanism for handling complaints is carried out by submitting complaints verbally and in writing to the maximum extent.